A Future Vision for Developing Techniques of Planning Social Programs and Projects at the Local Level - Kasas, Yasser Abd El Fatah El; Alabdulrazaq, Waleed Mohammed A. (Journal of Cultural Analysis and Social Change, 2025)
The formulation of a future vision for developing program and project planning techniques at the local level becomes a fundamental pillar in supporting sustainable development and improving the quality of life in local communities. Developing the techniques used in the preparation, implementation, and evaluation of programs and projects is a pivotal factor in enhancing efficiency, reducing waste, and achieving effective performance. Despite these important factors and the presence of national initiatives like the Egyptian Villages Development Project and Saudi Vision 2030, it is evident that there are still cumulative challenges affecting sustainable development in the local communities, and this is as a result of the ineffectiveness of traditional planning tools, the lack of community participation in developing policies, the inadequacy of technical competences, and shifting development priorities due to rapid economic and political transformations. This research aims to examine an integrated future vision for developing the techniques used in planning social programs and projects at the local level. A qualitative method based on content analysis was used to examine local planning data and extract development techniques. The findings reveal that for the future vision to succeed, several components must be considered: analyzing the reality, identifying key techniques, defining strategies, roles, and mechanisms, and proposing an implementation roadmap for gradual execution. These findings point out the importance of incorporating community participation and digital advancements into the suggested techniques. This connection aims to align local planning tools with governance, accountability, and efficiency standards, focusing on empowering the social planner as a key figure in community development. The study emphasizes the importance of effective planning methods in local social initiatives, highlighting their role in promoting sustainable growth and improving community welfare. It also offers a forward-looking perspective that combines modern planning techniques with traditional strategies, giving a new view on local development challenges.